Transition in vortex wakes of flow around an elliptic cylinder (Archives of Mechanics - Test, 2024)
Transition in the wake flow around an elliptic cylinder was numerically investigated at Reynolds numbers (Re) ranging from 3 to 200. The cylinder axis ratio (AR) varies from 0.125 to 8, while its angle of attack (AoA) was examined at 30°, 60°, and 90°. Simulation results reveal the existence of eight flow patterns, such as attached flow, steady symmetric vortex flow, steady asymmetric vortex flow, Kármán vortex street, double-periodical vortex shedding, Kármán wake followed by steady shear layers, Kármán wake followed by secondary wake, and chaotic flow. These flow patterns are strongly influenced by Re, AR, and AoA. The double-periodical vortex shedding wake contains two shedding frequencies. The spatial structure analysis shows that both small and large instabilities exist significantly in this pattern, while they are trivial in the Kármán wake. The Kármán wake followed by a secondary wake is characterized by symmetric like-signed spatial structures near the cylinder and distorted ones far downstream. Meanwhile, asymmetric spatial structures of various scales contribute most energy to a chaotic flow. Root mean square of the drag coefficient is high when vortex shedding occurs for three AoA, and a notable value is observed at AoA = 60°. Moreover, fluctuation of the lift coefficient at AoA = 90° is higher than those at AoA = 30° and 60°.